1995
DOI: 10.1681/asn.v61110
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter study of lipoprotein(a) and apolipoprotein(a) phenotypes in patients with end-stage renal disease treated by hemodialysis or continuous ambulatory peritoneal dialysis.

Abstract: Numerous studies have investigated lipoprotein(a) (Lp(a)) plasma concentrations in patients with ESRD, a patient group with an enormous risk for atherosclerosis. The reported differences in Lp(a) between controls and patients vary from a decrease of 49% to an increase of more than 1,000%. However, data are not consistent, mostly because of problems with statistical analysis, and only limited data are available for patients treated by continuous ambulatory peritoneal dialysis (CAPD). To estimate the significanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
3

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 216 publications
(20 citation statements)
references
References 48 publications
0
17
0
3
Order By: Relevance
“…Of note, the median Lp(a) levels increased as the kidney function impaired (11.0 at GFR >90, 18.4 at GFR 45–90 and 24.4 mg/dL at GFR <45 mL/min/1.73 m 2 ). These findings suggested that Lp(a) levels begin to increase even in early stages of kidney impairment [ 124 , 125 ] and showed an inverse association between Lp(a) levels and kidney function [ 125 , 126 ].…”
Section: Pathologies That Modify Lp(a) Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, the median Lp(a) levels increased as the kidney function impaired (11.0 at GFR >90, 18.4 at GFR 45–90 and 24.4 mg/dL at GFR <45 mL/min/1.73 m 2 ). These findings suggested that Lp(a) levels begin to increase even in early stages of kidney impairment [ 124 , 125 ] and showed an inverse association between Lp(a) levels and kidney function [ 125 , 126 ].…”
Section: Pathologies That Modify Lp(a) Concentrationsmentioning
confidence: 99%
“…Other studies have shown that the Lp(a) response was dependent on apo(a) sizes also during dialysis treatment. Apo(a) size specific increases in Lp(a) levels were seen among patients with NNKD or ESRD patients treated with HD [ 121 , 126 , 127 ]. Thus, Lp(a) levels were higher in HD patients compared with healthy controls (13.6 versus 9.2 mg/dL) as was the prevalence of a high Lp(a) level (23% versus 12%), despite a similar distribution of apo(a) isoforms in both groups [ 127 ].…”
Section: Pathologies That Modify Lp(a) Concentrationsmentioning
confidence: 99%
“…The average apoA‐IV concentrations in the general population are between 15 and 18 mg/dl [ 30 ]. We know from studies in the general population that apoA‐IV concentrations are an early marker of kidney impairment: concentrations start to increase early when eGFR decreases and albuminuria increases [ 30 ] and reach concentrations between 30 and 50 mg/dl in patients with kidney failure [ 33 , 34 ]. Immunohistochemical studies suggested that apoA‐IV is filtered by the glomerulus and is reabsorbed by tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…In case of the rare situation of very low or very high concentrations outside of the linear range, samples were repeated using a lower or higher dilution, respectively. The intra‐ and inter‐assay coefficients of variation were 2.7% and 6%, respectively [ 31 , 33 , 34 , 37 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation